Simulasi Kontrol Lampu Jarak Jauh Menggunakan Cisco Packet Tracer - Ahmad Royyan Fath; I Gede Surya Rahayuda (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
The advancement of Internet of Things (IoT) technology has significantly contributed to various aspects of modern life, particularly in smart home applications. One essential feature of a smart home is a remote light control system that enables users to manage household lighting more efficiently. This research simulates an IoT-based light control system using Cisco Packet Tracer, focusing on the design and implementation of a smart home network topology. The system consists of a Wi-Fi router, multiple smart lights, and a smartphone as the primary control device. The methodology includes network topology design, device configuration, and communication testing to evaluate system performance. The test results indicate that the system successfully operates according to the predefined scenarios, where smart lights respond to commands from a smartphone quickly and reliably via a Wi-Fi network. Additionally, the system demonstrates stable communication between IoT devices, even under network variations. This simulation highlights the potential of IoT-based light control systems in enhancing energy efficiency and providing greater convenience in home automation. Future research can expand this system by integrating sensor-based automation and cloud connectivity to improve flexibility, security, and scalability.